2021
DOI: 10.1097/pts.0000000000000830
|View full text |Cite|
|
Sign up to set email alerts
|

Avoidable Adverse Events Related to Ignoring the Do-Not-Do Recommendations: A Retrospective Cohort Study Conducted in the Spanish Primary Care Setting

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Multimorbidity, together with geriatric syndromes and frailty, frequently coexisting in the ageing process, increase clinical complexity and can lead to significant medicalization [ 9 ]. In these circumstances, there is an increased likelihood of low-value clinical practices, such as excessive polypharmacy and potentially inappropriate prescribing (PIP) [ 10 ]. These practices, in turn, may be determinant of certain adverse drug reactions (ADRs) or even mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity, together with geriatric syndromes and frailty, frequently coexisting in the ageing process, increase clinical complexity and can lead to significant medicalization [ 9 ]. In these circumstances, there is an increased likelihood of low-value clinical practices, such as excessive polypharmacy and potentially inappropriate prescribing (PIP) [ 10 ]. These practices, in turn, may be determinant of certain adverse drug reactions (ADRs) or even mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In absolute terms, this increase is higher in women (from 2.7% to 9.5%) than in men (from 2.3% to 8.5%). 12 In primary care, the SOBRINA study 13 showed that from 2018 to 2019, 55.1% of patients received at least one intervention classified as ‘Do Not Do’ related to benzodiazepines, Non-steroidal anti-inflammatory drugs (NSAIDs), lipid-lowering agents, antibiotics, paracetamol and ibuprofen. The percentage of medical records with more than one ‘Do Not Do’ was 18.5% in those over 29 years old.…”
Section: Introductionmentioning
confidence: 99%
“…1 LVC causes preventable adverse events for patients and wastes limited resources. [2][3][4] It has been estimated that 10%-25% of healthcare spending in the USA is related to LVC. 5 6 Prevalence estimations of inappropriate diagnostic testing range from 0.09% to 97.5%, indicating that the prevalence, along with the costs, highly depends on the type of care.…”
Section: Introductionmentioning
confidence: 99%
“…Low-value care (LVC) is either care that is not beneficial for patients or care for which the value does not offset the risk or cost given the available alternatives 1. LVC causes preventable adverse events for patients and wastes limited resources 2–4. It has been estimated that 10%–25% of healthcare spending in the USA is related to LVC 5 6.…”
Section: Introductionmentioning
confidence: 99%